2010
DOI: 10.1111/j.1365-2621.2010.02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a multidisciplinary approach to structuring in reduced saturated fat‐based systems – a review

Abstract: Although many food products are essentially emulsions, interest in the structuring of oil-continuous emulsions (and in specific cases water-continuous emulsions) is intense, particularly to meet the continuing challenge of reducing the degree of saturates in food systems. Consequently, it is necessary to observe the effects of structurants and to examine their impacts on current food systems. This is especially the case where novel structuring materials are used to wholly or partially replace traditional struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 102 publications
(356 reference statements)
0
40
0
1
Order By: Relevance
“…Removal of saturated and trans-fats from these products leads to loss of desirable textural attributes, such as plasticity, spreadability, and mouthfeel. A number of approaches have been investigated to create solid-like lipids with reduced levels of unhealthy saturated and trans-fats (Nehir El & Simsek, 2012;Wassell, Bonwick, Smith, Almiron-Roig, & Young, 2010). These approaches include the use of alternative sources of high melting lipids that form crystal networks (such as phytosterols, phytostanols, and waxes), the formation of gel-like association colloids using surface-active lipids (such as monoglycerides, phospholipids, or surfactants), and the utilization of multiple emulsions (Hughes, Marangoni, Wright, Rogers, & Rush, 2009;Lupi, Gabriele, de Cindio, Sanchez, & Gallegos, 2011;Rogers, 2009;Surh, Vladisavljevic, Mun, & McClements, 2007;Wassell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of saturated and trans-fats from these products leads to loss of desirable textural attributes, such as plasticity, spreadability, and mouthfeel. A number of approaches have been investigated to create solid-like lipids with reduced levels of unhealthy saturated and trans-fats (Nehir El & Simsek, 2012;Wassell, Bonwick, Smith, Almiron-Roig, & Young, 2010). These approaches include the use of alternative sources of high melting lipids that form crystal networks (such as phytosterols, phytostanols, and waxes), the formation of gel-like association colloids using surface-active lipids (such as monoglycerides, phospholipids, or surfactants), and the utilization of multiple emulsions (Hughes, Marangoni, Wright, Rogers, & Rush, 2009;Lupi, Gabriele, de Cindio, Sanchez, & Gallegos, 2011;Rogers, 2009;Surh, Vladisavljevic, Mun, & McClements, 2007;Wassell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidative phytochemical compounds in RBO include c-oryzanol (a mixture of ferulic acid esters of triterpene alcohols and phytosterols) and tocols (Gopala Krishna et al, 2001;Most et al, 2005). The RBO not only contains high amounts of antioxidants, but also high contents of phytosterols, which are well recognised as cholesterollowering phytochemicals (Moreau et al, 2002;Van Hoed et al, 2006;Wassell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that a relatively high intake of fat, especially trans and saturated fat, is a major contributor to the high incidence of coronary heart disease (Zevenbergen et al, 2009).Trans fatty acids are included among the dietary lipids that act as risk factors for coronary artery disease by modulating the synthesis of cholesterol and its fractions and acting on eicosanoids (Dhaka et al, 2011).Saturated fat is one of the main causes of the increase in plasma cholesterol, whose reduction in the diet is widely supported for reducing the risk of cardiovascular disease (Wassell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterols can be used as modifiers on the crystallization and structuring of lipids and to obtain lipid matrices with specific physical properties (Wassell et al, 2010). These changes occur due to different mechanisms: covalent bonds, hydrogen bonds, Van der Waals forces or steric entanglement, causing changes in solid profiles, melting points, consistency and other physical properties in fatty systems (Pernetti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%